Low-cost pick and place anthropomorphic robotic arm for the disabled and humanoid applications - Azlan, Norsinnira Zainul; Sanni, Mubeenah Titilola; Shahdad, Ifrah (Universitas Muhammadiyah Surakarta, 2020)
This paper presents the design and development of a new low-cost pick and place anthropomorphic robotic arm for the disabled and humanoid applications. Anthropomorphic robotic arms are weapons similar in scale, appearance, and functionality to humans, and functionality. The developed robotic arm was simple, lightweight, and has four degrees of freedom (DOF) at the hand, shoulder, and elbow joints. The measurement of the link was made close to the length of the human arm. The anthropomorphic robotic arm was actuated by four DC servo motors and controlled using an Arduino UNO microcontroller board. The voice recognition unit drove the command input for the targeted object. The forward and inverse kinematics of the proposed new robotic arm has been analysed and used to program the low cost anthropomorphic robotic arm prototype to reach the desired position in the pick and place operation. This paper’s contribution is in developing the low cost, light, and straightforward weight anthropomorphic arm that can be easily attached to other applications such as a wheelchair and the kinematic study of the specific robot. The low-cost robotic arm’s capability has been tested, and the experimental results show that it can perform basic pick place tasks for the disabled and humanoid applications.